Reconsideration of importance of the point mutation L982W in the voltage-sensitive sodium channel of the pyrethroid resistant Aedes aegypti (L.)(Diptera: Culicidae) in Vietnam. - Hitoshi Kawada; Yukiko Higa; Shinji Kasai (PLoS ONE)
Pyrethroid resistance in Aedes aegypti is widespread in southern Vietnam because the photostable 2nd generation pyrethroids have been used in large amounts over extensive areas for malaria and dengue vector control. In our previous report in 2009, F1534C, one of the point mutations in the voltage-sensitive sodium channel (VSSC) in Ae. aegypti, was widespread at high frequency in south and central area. However, no significant correlation between the frequency of F1534C and pyrethroid susceptibility was detected primarily because the F1534C mutation frequency in the southern highland area was very low, despite that the bioassay indicated high pyrethroid resistance. The point mutation in the VSSC, L982W, which was not the target mutation in our previous study, was recently determined to be an important mutation causing high-pyrethroid resistance in Vietnamese Ae. aegypti. In the present study, a re-investigation of L982W in the mosquito samples collected in 2006-2008 revealed a greater distribution of this mutation (allelic percentage 59.2%) than F1534C (21.7%) and the greater proportion of homozygous L982W as compared to F1534C provided a plausible answer to the question concerning the unknown resistance factor in the southern highland area. L982W frequencies were uniformly higher in the southern part of Vietnam, including the highland area with a significantly high positive correlation with pyrethroid resistance in Ae. aegypti.